Advances in Ultrasound Imaging in Rheumatology—What Do They Mean and What Challenges Do They Pose? The Example of Microvascular Imaging. (20th May 2021) - Almeida, Diogo Esperança; Costa, Emanuel; Cerqueira, Marcos
Abstract : Musculoskeletal ultrasound is an important tool for the monitorization of inflammatory rheumatic diseases, with subclinical synovitis being frequently detected in ultrasound scans of patients in clinical remission. It has been shown, for example, that the presence of Power Doppler signal synovial membrane has prognostic value for patients with rheumatoid arthritis. Microvascular imaging technologies significantly improve the sensitivity for slow‐flow vessels and may potentially detect subclinical inflammation when Power Doppler fails to do so. The authors briefly discuss the implications of the use of such techniques in rheumatology setting and review available evidence.